ANALYSIS OF IMMIGRATION ADMINISTRATION SANCTIONS ON FOREIGNERS IN INDONESIA - Wilonotomo Wilonotomo (Polteknik Imigrasi, 2018)
According to selective policy, only foreigners that can be beneficial for the welfare of the community, the nation and of the republic of indonesia and harmless security and order and not hostile good against the people, and the unitary state of the republic of indonesia which is permitted to enter or leave Indonesia. While the stranger who do dangerous activity and worthy of expected harm safety and public order or does not do legislations must be charged with the immigration administration sanction.The immigration administration sanction can be because the person is cubject to detterence, that is a ban on entering Indonesia territory.The most common immigration administration sanction is deportation, deportation is the act of forcibly removing foreigners of the indonesian territory.